The Identification of Crystalluria as an Early Picture of the Incidence of Urolithiasis in Cats in the Liliba Village - Angelina Sulistia Bheja; Tri Utami; Yohanes T.R.M.R Simarmata; Tarsisius C Tophianong (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Cats are one of the most common pets. One of the disorders than can affect cats is urolithiasis. Urolithiasis is a disease caused by the presence of urolith, calculi, crystals or excessive sediment in the urinary tract. This study was conducted to determine the peresence of crystalluria and its types in domestic cats in Liliba Village, Oebobo District, Kupang City. The samples used in this study were 15 samples of domestic cat urine. Urine collection was done by catheterization method, then physical examination of urine, sediment were carried out. The result showed the presence of crystalluria in 6 samples of cat urine consisting of 2 types of crystalluria, namely struvite crystals and calcium oxalate monohydrate crystals.